Alteration minerals, fluids, and gases on early Mars: Predictions from 1‐D flow geochemical modeling of mineral assemblages in meteorite ALH 84001. (16th August 2016) - Melwani Daswani, Mohit; Schwenzer, Susanne P.; Reed, Mark H.; Wright, Ian P.; Grady, Monica M.
Abstract: Clay minerals, although ubiquitous on the ancient terrains of Mars, have not been observed in Martian meteorite Allan Hills (ALH) 84001, which is an orthopyroxenite sample of the early Martian crust with a secondary carbonate assemblage. We used a low‐temperature (20 °C) one‐dimensional (1‐D) transport thermochemical model to investigate the possible aqueous alteration processes that produced the carbonate assemblage of ALH 84001 while avoiding the coprecipitation of clay minerals. We found that the carbonate in ALH 84001 could have been produced in a process, whereby a low‐temperature ( 20 °C) fluid, initially equilibrated with the early Martian atmosphere, moved through surficial clay mineral and silica‐rich layers, percolated through the parent rock of the meteorite, and precipitated carbonates (thereby decreasing the partial pressure of CO2 ) as it evaporated. This finding requires that before encountering the unweathered orthopyroxenite host of ALH 84001, the fluid permeated rock that became weathered during the process. We were able to predict the composition of the clay minerals formed during weathering, which included the dioctahedral smectite nontronite, kaolinite, and chlorite, all of which have been previously detected on Mars. We also calculated host rock replacement in local equilibrium conditions by the hydrated silicate talc, which is typically considered to be a higher temperature hydrothermal phase on Earth, but may have been a common constituent in the formation of Martian soils through pervasive aqueous alteration. Finally, goethite and magnetite were also found to precipitate in the secondary alteration assemblage, the latter associated with the generation of H2 . Apparently, despite the limited water–rock interaction that must have led to the formation of the carbonates 3.9 Ga ago, in the vicinity of the ALH 84001 source rocks, clay formation would have been widespread.